A salt-assisted acid etching strategy for hollow mesoporous silica/organosilica for pH-responsive drug and gene co-delivery. Issue 5 (3rd December 2014) - Wu, Meiying; Chen, Yu; Zhang, Lingxia; Li, Xiaoyu; Cai, Xiaojun; Du, Yanyan; Zhang, Linlin; Shi, Jianlin
Abstract : Hollow mesoporous organosilica nanoparticles have been developed by a salt-assisted acid etching strategy and employed to co-deliver DOX and shRNA. Abstract : A salt-assisted acid etching (SAAE) strategy has been developed to construct rattle/hollow mesoporous silica/organosilica nanovehicles (R/HMSVs or R/HMOVs), which settles the drawbacks of traditional silica etching approaches, such as undesirable by-products, by alkaline etching and strong corrosion of the HF etching process. The hollow structure and phenylene-bridged framework of HMOVs were found to be responsible for the high cargo-loading capacity and pH-responsive drug releasing behavior, respectively, based on the special cargo-framework interaction. Especially, the molecularly organic–inorganic hybrid HMOVs have been, for the first time, successfully engineered to concurrently deliver anticancer drugs and P-gp-associated shRNA molecules for enhancing the intracellular drug concentrations and reversing the multidrug resistance (MDR) of cancer cells. On the basis of this special SAAE strategy, a wide range of mesoporous silica-based hollow nanostructures are anticipated to be synthesized to satisfy the strict requirements in various nano-catalytic and biomedical applications.